From Andes to Amazon: Assessing Branched Tetraether Lipids as Tracers for Soil Organic Carbon in the Madre de Dios River System. Issue 1 (17th January 2020) - Kirkels, Frédérique M. S. A.; Ponton, Camilo; Galy, Valier; West, A. Joshua; Feakins, Sarah J.; Peterse, Francien
Abstract: We investigate the implications of upstream processes and hydrological seasonality on the transfer of soil organic carbon (OC) from the Andes mountains to the Amazon lowlands by the Madre de Dios River (Peru), using branched glycerol dialkyl glycerol tetraether (brGDGT) lipids. The brGDGT signal in Andean soils (0.5 to 3.5 km elevation) reflects air temperature, with a lapse rate of −6.0 °C/km elevation ( r 2 = 0.89, p < 0.001) and −5.6 °C/km elevation ( r 2 = 0.89, p < 0.001) for organic and mineral horizons, respectively. The same compounds are present in river suspended particulate matter (SPM) with a lapse rate of −4.1 °C/km elevation ( r 2 = 0.82, p < 0.001) during the wet season, where the offset in intercept between the temperature lapse rates for soils and SPM indicates upstream sourcing of brGDGTs. The lapse rate for SPM appears insensitive to an increasing relative contribution of 6‐methyl isomer brGDGTs produced within the river. River depth profiles show that brGDGTs are well mixed in the river and are not affected by hydrodynamic sorting. The brGDGTs accumulate relative to OC downstream, likely due to the transition of particulate OC to the dissolved phase and input of weathered soils toward the lowlands. The temperature‐altitude correlation of brGDGTs in Madre de Dios SPM contrasts with the Lower Amazon River, where the initial soil signature is altered by changes in seasonal in‐river production and variable provenance of brGDGTs. Our study indicates that brGDGTs in the Madre de Dios River system are initially soil derived and highlights their use to study OC sourcing in mountainous river systems. Plain Language Summary: Rivers transport large amounts of carbon from soils to the ocean. However, following the route of carbon from mountains to river to sea is challenging in part due to the reactive nature of organic molecules in the environment. In this paper, we investigated the Madre de Dios (Peru), an upstream branch of the Amazon River, and identified carbon sources using temperature‐sensitive compounds. The expected correlation between altitude and temperature is found for soil and river material. The origin of river material is predominantly upstream soils and constant with river depth. Upon reaching the lowlands, input from weathered soils and lowland tributaries changed the compound distributions in the river main stem. Lowland soil input and/or in‐river microbial production become an increasingly important source and overprint the mountain‐sourced signal. Thus, the temperature‐sensitive compounds appear to be useful to study carbon sources in mountain watersheds. Furthermore, comparing our data (headwaters) with the downstream Amazon River shows that lowland soils and/or in river production seem to dominate the signal finally exported to the ocean. Key Points: Bacterial membrane lipids (brGDGTs) in soils from Madre de Dios catchment, Peru, record temperature The brGDGTs in river suspended matter reflect their catchment and accumulate downstream The brGDGTs primarily trace soil organic carbon in the Madre de Dios River system